2020
DOI: 10.1088/1402-4896/abc03e
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer analysis of viscoelastic fluid flow with fractional Maxwell model in the cylindrical geometry

Abstract: This investigation deals with the study of heat transfer analysis of fractional Maxwell fluid in a vertical circular cylinder which is initially at rest. Semi-analytical elucidations for velocity as well as temperature fields have been established by using a hybrid technique which has less time cost and mathematical calculations as compared to other techniques existing in the literature. This problem is also solved exactly with the help of integral transform technique which involves Laplace along with finite H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Most of these problems are traced to specific areas of engineering, namely, the sciences, economics, and social sciences. Recently, several studies have investigated the performance of CG methods on different application problems, such as robotic motion control, compressive sensing, fuzzy nonlinear problems, and inverse heat transformation problems (see Umar et al, 2020;Sulaiman et al, 2022bSulaiman et al, , 2022cRazzaq et al, 2020;. This section examines the inverse heat transformation problem.…”
Section: Application Of the Ttumw Methods For Function Estimation In ...mentioning
confidence: 99%
“…Most of these problems are traced to specific areas of engineering, namely, the sciences, economics, and social sciences. Recently, several studies have investigated the performance of CG methods on different application problems, such as robotic motion control, compressive sensing, fuzzy nonlinear problems, and inverse heat transformation problems (see Umar et al, 2020;Sulaiman et al, 2022bSulaiman et al, , 2022cRazzaq et al, 2020;. This section examines the inverse heat transformation problem.…”
Section: Application Of the Ttumw Methods For Function Estimation In ...mentioning
confidence: 99%
“…In 2016, Karthikeyan et al 10 investigated numerically on MHD mixed convection flow with heat, mass transfer through a vertical plate in an absorptive medium with chemical reaction, radiation, and heat generation. Some of the other studies related to the above phenomena are found in previous studies 11‐17 . Mushtaq et al 18 presented the article related to the impact of thermal radiation with the help of different applications of Rosseland conjecture on fluid flow type of viscoelastic over a stretching plate with different heating processes.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies have shown that integer-order models are the limited case of the generalized Maxwell model. The authors of [24] improved the method in [23] by mixing the Hankel transform and Laplace transform techniques, effectively reducing the difficulty of theoretical derivation. The results showed that parameters such as the order and Prandtl number have a significant impact on heat transfer.…”
Section: Introductionmentioning
confidence: 99%